2022
DOI: 10.3390/biomedicines10061416
|View full text |Cite
|
Sign up to set email alerts
|

PARP Inhibitors: A New Horizon for Patients with Prostate Cancer

Abstract: The introduction of PARP inhibitors (PARPi) in prostate cancer is a milestone and provides a pathway to hope in fighting this disease. It is the first time that drugs, based on the concept of synthetic lethality, have been approved for prostate cancer. In addition, it is also the first time that genetic mutation tests have been included in the therapeutic algorithm of this disease, representing a significant step forward for precision and personalized treatment of prostate cancer. The objectives of this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 112 publications
0
23
0
Order By: Relevance
“…Talazoparib has a trapping efficiency nearly one hundred times more potent than that of niraparib, followed by olaparib and rucaparib [ 87 , 88 , 89 ]. While higher trapping efficiency may potentially be more effective, it has been associated with more toxicity [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Talazoparib has a trapping efficiency nearly one hundred times more potent than that of niraparib, followed by olaparib and rucaparib [ 87 , 88 , 89 ]. While higher trapping efficiency may potentially be more effective, it has been associated with more toxicity [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…ADT may induce the downregulation of these DDR genes, promoting increased cancer cell death [ 119 ]. Consequently, subsequent increased PARP activity can lead to tumor-cell survival and modulation of AR-axis activity [ 90 ], which in turn can be countered by PARP inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have conclusively demonstrated that genomic alterations in DNA damage repair (DDR) genes are prevalent in both primary and metastatic PCa tissue [36], leading to the clinical utilisation of PARP inhibitors (PARPi) in patients with DDR de ciencies [37]. However, the emergence of resistance mechanisms has been observed in patients receiving PARPi treatment [38].…”
Section: Pde4d7 Speci C Knockdown In Lncaps Is Associated With Expres...mentioning
confidence: 99%
“…BRCA mutated tumor cells are 1000-fold more sensitive to PARP inhibitors than BRCA wild-type cells (15). Hence, the development of PARP inhibitors initially emphasized the population with BRCA1/2 gene mutation.…”
Section: Mechanism Of Action Of Parp Inhibitorsmentioning
confidence: 99%